Pathogenicity and whole-genome analysis of a Siniperca chuatsi-derived Nocardia seriolae strain - Chen, Liting; Yan, Xin; Luo, Yongju; Lu, Zhuanling; Wei, Xinxian; Tang, Zhanyang; Xia, Liqun; Chen, Fuyan; Li, Ming; Guo, Zhongbao; He, Zhichang; Huang, Ting (Frontiers in Microbiology, 2025)
A bacterial strain (No. 20230510) was isolated from the kidneys of diseased Siniperca chuatsi in Guangxi, China, since 2023. Artificial infection experiments demonstrated that this strain caused the observed disease in S. chuatsi. The isolate underwent morphological, pathological, genomic (whole-genome sequencing, WGS), and antibiotic susceptibility analyses. Infection trials revealed 100% mortality in high-concentration groups, with an LD50 of 3.89 × 104 CFU/mL, indicating high virulence. WGS results showed a circular chromosome of 8,123,106 bp (GC content: 68.14%), containing 7,638 CDSs, 72 tRNAs, and 12 rRNAs. Phylogenomic analysis revealed that strain 20230510 (CP130742) clusters with three N. seriolae strains with 98% bootstrap supporting, confirming its identification as N. seriolae. Further analysis identified 403 potential virulence genes linked to nutrient metabolism, regulatory factors, immune modulation, effector delivery systems, and exotoxins. Chromosomal comparisons also detected multiple antibiotic resistance genes. Susceptibility testing confirmed sensitivity to nine antibiotics, including enrofloxacin, doxycycline, florfenicol, and sulfamethoxazole. Histopathology revealed chronic granulomatous lesions, most severe in the kidneys, with similar but milder damage in the liver, spleen, gills, and intestines. These results confirm N. seriolae strain 20230510 as the pathogenic agent behind S. chuatsi mortality, offering key insights for developing control strategies.